Effect of post-space irrigation with acid solutions on bond strength and dentin penetrability using a self-adhesive cementation system - Silva, Aryvelto-Miranda [UNESP]; Alencar, Cristiane-De Melo [UNESP]; Jassé, Fernanda-Ferreira-De Albuquerque; Pedrinha, Victor-Feliz; Zaniboni, Joissi-Ferrari [UNESP]; Dantas, Andréa-Abi-Rached [UNESP]; de Campos, Edson-Alves [UNESP]; Kuga, Milton-Carlos [UNESP] (Medicina Oral, S.L., 2021)
Background: The aim of this study was to evaluate the effects of surface treatments with 1% peracetic acid (PA), solution containing 17% EDTA (SmearClear, Kerr Endodontics), solution containing a combination of 17% EDTA with 2% chlorhexidine (QMix, Dentsply Sirona) on the post-space root dentin compared to 2.5% sodium hypochlorite (NaOCl) on bond strength and resin tags length in dentin. Material and Methods: Forty human-canine roots were endodontically treated and the post space was prepared. The specimens were randomised into four groups (n = 10): control - irrigation with 2.5% NaOCl solution, PA - irrigation with 1% PA, SmearClear - irrigation with SmearClear solution, and QMix - irrigation with QMix solution. The fibre posts were cemented using a self-adhesive resin system (Relyx U200, 3M ESPE). After six months, the specimens were cross-sectioned and subjected to push-out and confocal laser microscopy tests. One-way ANOVA and Tukey's tests were used to analyse the data (a= 0.05). Results: PA and QMix presented the highest bond strength values compared to the other groups (p < 0.05). There was no significant difference between the resin tags length in dentin by the groups (p = 0.75). Conclusions: Irrigation of the post space with 1% PA and QMix showed a positive clinical impact on the adhesion between the fiber post and root dentin. However, these materials had no influence on resin tags length in dentin by self-adhesive resin cement.
Keywords: adhesive cementation; Fiber post; irrigating solutions; root dentin; self-adhesive resin cement